Adhesive Interactions Delineate the Topography of the Immune Synapse - Martín-Cófreces, Noa Beatriz; Vicente-Manzanares, Miguel; Sánchez-Madrid, Francisco (Frontiers in Cell and Developmental Biology, 2018)
T cells form adhesive contacts with antigen-presenting cells (APCs) as part of the normal surveillance process that occurs in lymph nodes and other tissues. Most of these adhesive interactions are formed by integrins that interact with ligands expressed on the surface of the APC. The interactive strength of integrins depends on their degree of membrane proximity as well as intracellular signals that dictate the conformation of the integrin. Integrins appear in different conformations that endow them with different affinities for their ligand(s). Integrin conformation and thus adhesive strength between the T cell and the APC is tuned by intracellular signals that are turned on by ligation of the T cell receptor and chemokine receptors. During the different stages of the process, integrins, the TCR and chemokine receptors may be interconnected by the actin cytoskeleton underneath the plasma membrane, forming a chemical and physical network that facilitates the spatiotemporal dynamics, positioning and function of these receptors and supports cell-cell adhesion during T cell activation, allowing it to perform its effector function.